Development and Validation of a Predictive Model for Spontaneous Hemorrhagic Transformation After Ischemic Stroke - Wei, Chenchen; Liu, Junfeng; Guo, Wen; Jin, Yuxi; Song, Quhong; Wang, Yanan; Ye, Chen; Li, Jing; Zhang, Shanshan; Liu, Ming (Frontiers in Neurology, 2021)
Background: HT after reperfusion therapy for AIS has been well studied, however, there is scarce research focusing on spontaneous HT (sHT). Spontaneous HT is no less important with a relatively high incidence and could be associated with neurological worsening. We aimed to develop and validate a simple and practical model to predict sHT after AIS (SHAIS), and compared the predictive value of the SHAIS score against the models of post-reperfusion HT for sHT. Methods: Patients with AIS admitted within 24 hours of onset were prospectively screened to develop and validate the SHAIS score. The primary outcome was sHT during hospitalization (within 30 days after onset), and the secondary outcomes were symptomatic sHT and parechymal hemorrhage (PH). Clinical information, laboratory and neuroimaging data were screened to construct SHAIS score. We selected six commonly used scales for predicting HT after reperfusion therapy, and compared their predictive ability for sHT with the SHAIS score using Delong’s test. Results: The derivation cohort included 539 patients (mean age, 68.1 years; men, 61.4%), of whom 91 (16.9%) patients developed sHT with 25.3% (23/91) being symptomatic sHT and 62.6% (57/91) being PH. Five variables (atrial fibrillation, NIHSS score≧10, hypodensity >1/3 of middle cerebral artery territory, hyperdense artery sign and anterior circulation infarction) composed the SHAIS score, which ranged from 0 to 11 points. The area under the receiver-operating characteristic curve (AUC) was 0.86 (95% CI 0.82-0.91, p<0.001) for the overall sHT, 0.85 (95% CI 0.76-0.92, p<0.001) for symptomatic sHT and 0.89 (95% CI 0.85-0.94, p<0.001) for PH. No evidence of miscalibration of the SHAIS score was found to predict the overall sHT (p=0.19), symptomatic sHT (p=0.44), and PH (p=0.22). The internal (n=245) and external validation cohorts (n=200) depicted similar predictive performance compared to the derivation cohort. The SHAIS score had a higher AUC to predict sHT than any of the six pre-existing models (p<0.05). Conclusions: The SHAIS score provides an easy-to-use model to predict sHT, which could help providers with decision-making about treatments with high bleeding risk, and to counsel patients and families on the baseline risk of HT, aligning expectations with probable outcomes.